PENGARUH LAMA FERMENTASI KACANG GUDE (Cajanus cajan L.) TERHADAP KARAKTERISTIK “SERE UNDIS” - Febriani, Ni Luh Cintya; Suparthana, I Putu; Wiadnyani, Anak Agung Istri Sri (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2019)
This study aims to determine effect of fermentation time pigeon pea on the characteristics of sere undis and determine the optimum fermentation time in making sere undis with the best characteristics. The design used in this research is Completely Randomized Design (RAL) with one factor that is fermentation time which consisting of 5 experimental levels that were 12,18,24,30 and 36 hours. The treatment was repeated 3 times to obtain 15 units of experiment.  Fermentation time of pigeon pea influenced the content of water, ash, protein, fat, carbohydrate, and antioxidant capacity but did not affect crude fiber, sensory character of sere undis has significant effect on aroma and taste but no significant effect on color, texture and the fermentation time of 24 hour pigeon pea produced sere undis with the best characteristic: water content 26,36%, ash content 0,95%, protein content 8,24%, fat content 16,67%, carbohydrate 47,78%, crude fiber 9,52%, antioxidant capacity 83,49% and sensory properties were ordinary for color, like for texture, rather like for aroma, sense, and overall acceptance.